Postnatal and neonatal care after home birth: A community-based study in Nepal. - Karkee, R.; Khanal, Vishnu (Elsevier BV, 2016)
Background: In Nepal, the majority of women who give birth at home do not visit a health facility for postnatal and neonatal care. Objectives: This study investigated postnatal and neonatal care practices of women who give birth at home in a central hills district of Nepal. Design: This study is a part of community-based prospective study in the Kaski district of Nepal. Postnatal and neonatal care practices were collected via structured questionnaires. Setting: Kaski district of Nepal. Participants: 92 postpartum women who gave birth at home. Outcome measures: Postnatal care at a health facility and neonatal care practices. Findings: Approximately 90% (83/92) of women who gave birth at home were assisted by non-skilled birth attendants, and 67% (62/92) received no postnatal care at a health facility within a week post delivery. The main reason for not having postnatal care at a health facility was ‘no perceived need’ (52/ 62, 83.9%). With regard to neonatal care practices, 67% (62/92) used a delivery kit, 79% (73/92) washed their hands before handling their babies, 70% (64/92) bathed their babies on the second day of birth, while all dried and wrapped their babies with a cloth within half an hour of the birth. However, only 46% (42/92) reported skin-to-skin contact within one hour after birth. Conclusions: The results suggest that there is great scope to strengthen community-based postnatal and neonatal care to screen for and identify postnatal and neonatal problems, especially at home birth.